Hydrodynamic mechanism analysis of the pump hump district for a pump-turbine. Issue 3 (3rd May 2016) - Xiao, Yexiang; Yao, Yangyang; Wang, Zhengwei; Zhang, Jin; Luo, Yongyao; Zeng, Chongji; Zhu, Wei
Abstract : Purpose: – The purpose of this paper is to numerically analyze the flow characteristic and explore the hydrodynamic mechanism of the pump mode hump district formation of a Francis pump-turbine. Design/methodology/approach: – Numerical simulations were conducted of the entire pump-turbine flow passage under different discharge conditions by adopting the SST-CC turbulence model. The internal flow at hump district has been explained in detail combined with the model test in this paper. The unsteady flow and pressure fluctuation characteristics are analyzed under five different discharge conditions in the hump and nearby region. The reason of the hump district formation is explored combined with the flow components hydraulic loss. Findings: – The large hydraulic loss, high relative peak-to-peak amplitudes and low dominant frequencies are on account of the disorganized internal flow condition. The formation of the hump district is concerned with the large hydraulic loss inside the draft tube, runner and guide vanes as there occurs secondary flow, backflow even vortex in the hump district. In addition, the low dominant frequencies at recording points inside the flow passage are always accompanied with the change of flow patterns and the spreading of the pressure fluctuations. Originality/value: – The analysis method of each flow components hydraulic loss combined with internal flow structure is adopted to explore the mechanism of pump mode hump characteristic. The flow characteristic and pressure pulse characteristics all correspond to the flow components hydraulic loss.